Framing Analysis of Mirna’s Father in the Documentary Film “Ice Cold: Murder, Coffee, and Jessica Wongso” - Persada, Muhammad Rizqi; Fajrini, Nurkhalila (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Documentary films serve as powerful media for conveying messages and stories to audiences. Netflix released a documentary titled